Effects of certain micronutrients and melatonin on plasma lipid, lipid peroxidation, and homocysteine levels in rats - Baydas, G; Yilmaz, O; Celik, S; Yasar, A; Gursu, MF (Elsevier Science Inc, 2002)
Background. Numerous studies suggest an association between high intake of antioxidant vitamins and fish oil and reduced risk of coronary heart disease. Hyperhomocysteinemia has also been identified as an independent risk factor for arteriosclerosis. In this paper, we aimed to evaluate the effects of vitamin E, vitamin C, vitamin C 6 palmitate (VC6P), lipoic acid, fish oil, and melatonin supplementation on lipid peroxidation, plasma lipid, and homocysteine (Hcy) levels in rats. Methods. Animals were divided into seven groups: one was used as control and each remaining group was supplemented with one substance for 6 weeks. All substances were dissolved in olive oil and injected intraperitoneally (i.p.) with the exception of vitamin-C, which was dissolved in drinking water. Plasma Hcy, lipid peroxidation, and lipids were determined. Results. Plasma malondialdehyde (MDA) levels decreased significantly in melatonin (p < 0.01), lipoic acid (p < 0.01), and vitamin E (p < 0.05) groups. On the other hand, supplementation with vitamin C and VC60P lowered MDA levels moderately but not significantly (p > 0.05). Fish oil supplementation caused a slight but insignificant increase in plasma MDA levels (p > 0.05). Plasma lipid levels in animals treated with melatonin, vitamin E, vitamin C, lipoic acid, and fish oil were significantly lower than those of controls; however, treatment of rats with VC6P has no significant effect on plasma lipid level. Melatonin and fish oil administration significantly lowered plasma Hcy levels, whereas VC6P elevated its level. There was no significant effect of vitamin E, vitamin C, and lipoic acid on levels of plasma Hcy. Conclusions. Our data suggest that supplementation with antioxidants appears to be hypolipidemic. In addition to these beneficial effects, administration of melatonin and fish oil deserves careful consideration as a measure to lower plasma Hcy levels and reduce risk of cardiovascular diseases. (C) 2002 IMSS. Published by Elsevier Science Inc.
Keywords: homocysteine; vitamins; melatonin; fish oil; lipids